MO982: Determinants of Coronary Artery Calcium Score in Stable Kidney Transplant Recipients 12 Months After Transplantation. (3rd May 2022) - Guedes Rodrigues, Fernanda; Bruins, Megan; Vliegenthart, Rozemarijn; Sotomayor Campos, Camilo; Kremer, Daan; Navis, Gerjan; J.L. Bakker, Stephan; De Borst, Martin; Keyzer, Charlotte
Abstract: BACKGROUND AND AIMS: Cardiovascular disease remains the primary cause of death after kidney transplantation. Vascular calcification may at least in part explain excess cardiovascular morbidity and mortality, but little is known about the drivers of vascular calcification after kidney transplantation. Remarkably, some patients with kidney failure develop extensive calcifications, whereas others remain free of calcifications. This study aimed to assess the severity of CAC score and investigate potential determinants of vascular calcification in stable kidney transplant recipients (KTRs) at 12 months after transplantation. The second aim was to compare the characteristics of KTRs without any calcifications versus those with a relatively high CAC score. METHOD: Adult KTRs with no prior coronary artery disease and eGFR >30 mL/min/1.73 m 2 who visited our center between June 2018 and June 2021 underwent non-contrast computed tomography (CT) of the heart to quantify the coronary artery calcium (CAC)-score, calculated by the Agatston method. CAC-score percentiles were calculated using a CAC nomogram available at https://www.calciumscorecalculator.com . Clinical, laboratory, lifestyle and nutritional data, including bioimpedance analysis (BIA), were collected as part of the TransplantLines Biobank and Cohort Study1. The association between potential determinants and CAC-score percentiles was first studied in univariable multinomial logistic regression analysis and subsequently all variables with P < 0.10 were included in a multivariable multinomial logistic regression analysis to study independent determinants of CAC. We subsequently performed a case control analysis, comparing KTRs without calcifications (no-CAC, n  = 36) versus those with relatively high calcium score (CAC ≥75th percentile, n  = 36), matched by age, sex and dialysis vintage. RESULTS: A total of 203 KTRs (54.0 ± 14.7 year old, 61.1% male) at 12 months after transplantation were included in the main analysis. Participants were categorized into three groups according to CAC-score percentiles {P = 0% (CAC = 0), n  = 68; P ≥1%—P ≤ 75% [CAC = 67.5 (6.5–247.0)], n  = 52; P > 75%, [CAC = 0], 581 (148.0–1652), n  = 83}. Individuals in the highest CAC-score percentile group had lower educational level, heart rate, urinary protein excretion, urinary magnesium excretion, physical functioning score and phase angle assessed by BIA (a marker of both hydration status and body cell mass/integrity), and higher prevalence of diabetes mellitus, dialysis vintage, serum triglycerides, PTH, alkaline phosphatase, calcium, use of statins, use of antihypertensives and use of diuretics. In multivariable-adjusted multinomial logistic regression analysis, donor living status and phase angle were inversely associated with CAC-score >75% (Table 1 ). In the matched case control analysis, KTR with CAC-score >75% had lower plasma magnesium, albuminuria, and phase angle, and were less likely a recipient from a living donor (Table 2 ). CONCLUSION: This study identifies phase angle, reflecting body cell integrity, as an independent determinant of CAC at 12 months after kidney transplantation. Interestingly, in two subgroups with similar dialysis vintage, KTRs with a CAC score of zero were more likely to have received a kidney from a living donor, and had higher plasma magnesium levels, compared with KTRs with relatively high CAC scores. Futures studies should address whether improving magnesium status could retard calcification progression after kidney transplantation.